SOSIALISASI PENTINGNYA PENYUSUNAN LAPORAN KEUANGAN PADA USAHA KECIL MENENGAH DI DESA KOTA PARI KEC. PANTAI CERMIN - Fachruddin, Wan; Aliah, Nur (Jurnal Pengabdian Bukit Pengharapan, 2023)
The purpose of carrying out this community service activity (PkM) is to socialize the importance of preparing financial reports for SMEs in Kota Pari village, Pantai Cermin District. This outreach is carried out directly to village communities who especially have businesses. The types of businesses owned by village communities include grocery businesses, salon businesses, palm sugar making businesses, fast shrimp making businesses and so on. The enthusiasm of the community when this socialization was carried out was very good, they had a lot of discussions in this activity about how to create and compile financial reports for their business according to the type of business they are running.